A primeira escola secundária pública de Cascavel: O Ginásio Wilson Joffre (1960-1980) - Nath, Valdecir Antonio (2013)
This dissertation entitled The first public high school in Cascavel: the gym Wilson Joffre (1960-1980), lies in the field of history of scholastic institutions. Object of study is the first secondary school, public gym Cascavel, founded in 1959. The main objective of the research was to discuss the genesis of this institution, considering the elements of the social, political and economic times, as well as the implications for its structure. The research points to the regional political interference, the student mobilization in the maintenance of the school as its expansion in care due to the growing demand from the process of urbanization and modernization which passed by the municipality. The reconstruction of the history of the State College Wilson Joffre shows the fragility of the public when it comes to public school. We seek to identify the main elements that constitute its history. We hypothesized that the Gym, today located in the city center, was at the time of its foundation, a school of elites, which will be confirmed in the course of this work. Its architecture and location of your installation is not up to the standard of a school typically bourgeois, however, in the case of Rattlesnake effectively contributed to the formation of political and economic leaders that are now part of the elite Cascavel and studied at the gym. The gym suffered the interference of political struggles local, regional and national seeking to assert their interests, especially with regard to curriculum, adjusting to the determinations in the first moment of Law No. 4024/61 and after the Reform of Teaching First and Second Degrees, Law No. 5692/71, which guided and normalized secondary education in Brazil. Access to sources was one of the great challenges of this work, since many documents were lost, limiting data and establishing some gaps in the research. This is the documentary analysis, comparing its contents with the data of reality, memory, built by local elites, networks of interest, social projects in dispute, establishing the light of the literature referenced, especially in Gramsci, Buffa, Nosella and Saviani. We seek to grasp the historical significance of the theoretical and ideological statements by the social, political and economic context in which they were produced.